Предмет: Алгебра,
автор: katy263
(1+tg^2a)cos^2a+sin^2a(1+ctg^2a)
1+2sinx
cos(a-бета)+sin(-a)sinбета=cosa*sinбета
Срочно
Ответы
Автор ответа:
0
(1+tg^2a)cos^2a+sin^2a(1+ctg^2a)=1/cos²a*cos²a+sin²a*1/sin²a=
=1+1=2
cos(a-b)+sin(-a)sinb=cosasinb
cos(a-b)+sin(-a)sinb=cosacosb+sinasinb-sinasinb=cosacosb
=1+1=2
cos(a-b)+sin(-a)sinb=cosasinb
cos(a-b)+sin(-a)sinb=cosacosb+sinasinb-sinasinb=cosacosb
Похожие вопросы
Предмет: Математика,
автор: shepelevayaroslava
Предмет: Алгебра,
автор: Sashasashabrijak
Предмет: Алгебра,
автор: uidsfuiosddj8otg
Предмет: Английский язык,
автор: ArishkaTeltevskaya
Предмет: Химия,
автор: djksjcjc